Vaticanus Distigme-obelos Symbols Marking Added Text, Including 1 Corinthians 14.34-5 - Payne, Philip Barton (New Testament studies, 2017)
The two-dot-plus-bar distigme-obelos' symbols in Vaticanus signal added text. Five characteristic features distinguish their obeloi from paragraphoi. Like scribe B's LXX obeloi, all eight distigme-obelos symbols mark the location of added text. A gap at the exact location of a widely recognised, multi-word addition follows every distigme-obelos except one with distinctive downward dipping strokes. The Vaticanus Gospels are so early that they have virtually no high stops, a feature older than even 75. Consequently, they contain none of these additions, but the Vaticanus epistles have high stops throughout and contain their one distigme-obelos-marked addition, 1 Cor 14.34-5. Contemporaneous LXX G has corresponding distigmai.